It makes huge sense that this is true but how to prove it using a truth table? I have started by making a truth table for $(a \leftrightarrow b)$ first:
a b a↔b
----------------------
0 0 1
0 1 0
1 0 0
1 1 1
For $a \rightarrow b$ we have:
a b a→b
----------------------
0 0 1
0 1 1
1 0 0
1 1 1
And $b \rightarrow a$ we have:
a b b→a
----------------------
0 0 1
0 1 0
1 0 1
1 1 1
And now I can see that the second and third lines of the second and third table contradict each other, which means we can just erase them. In the end we have 1 0 0 1 which equals the first table.
How would you solve this task? As I just described? Or would I have to do this $(a \rightarrow b) \wedge (b \rightarrow a)$ ALL in one table? Please do tell me.
Edit: Can I do it like this?